The Relationship Between Listening Skills and Arabic Writing Skills - Khaerati, Nur (Al-Iftah: Journal of Islamic studies and society, 2023)
This article discusses the relationship between listening skills and Arabic writing skills in Class X MA DDI Ujung Lare Parepare students. This research uses a quantitative type of research. This research is correlation research. The results of this research show: 1) The total score for the Arabic listening skills variable obtained from the research results is 3477: 4000 = 0.869 or 86.9% of the specified criteria, and is in the high category. 2) The total variable score on Arabic writing skills for Class 3) Based on the t valuecountof 3.811 is consulted with the t value table (3.811 > 0.681, meaning that there is a significant correlation or relationship between listening skills and Arabic writing skills in Class X MA DDI Ujung Lare Parepare students. Keywords: Listening Skills, Arabic writing skills.